Estimating the SARS-CoV-2 infection fatality rate by data combination: the case of Germany's first wave. Issue 2 (29th January 2022) - Dimpfl, Thomas; Sönksen, Jantje; Bechmann, Ingo; Grammig, Joachim
Summary: Assessing the infection fatality rate (IFR) of SARS-CoV-2 in a population is a controversial issue. Due to asymptomatic courses of COVID-19, many infections remain undetected. Reported case fatality rates are therefore poor estimates of the IFR. We propose a strategy to estimate the IFR that combines official data on cases and fatalities with data from seroepidemiological studies in infection hotspots. The application of the method yields an estimate of the IFR of wild-type SARS-CoV-2 in Germany during the first wave of the pandemic of 0.83% (95% CI: [0.69%; 0.98%]), notably higher than the estimate reported in the prominent study by Streeck et al. (2020 ) (0.36% [0.17%; 0.77%]) and closer to that obtained from a world-wide meta analysis (0.68% [0.53%; 0.82%]), where the difference can be explained by Germany's disadvantageous age structure. Provided that suitable data are available, the proposed method can be applied to estimate the IFR of virus variants and other regions.